Energy transition as a path to sustainable development in Latin American countries - Diana Pamela Chavarry Galvez; Svetlana Y. Revinova (Unconventional Resources)
This article examines key aspects of the energy transition as a pathway towards sustainable development in the Latin American region. The main directions of energy transition are highlighted, the role of alternative energy as a crucial driver is explored, and an analysis of progress towards energy transition goals in Latin America is presented. The study identifies challenges hindering the energy transition, including climate change, financial constraints, technological limitations, socio-economic disparities, and organizational barriers. To address these issues, the following measures are proposed: improving the institutional framework; strengthening policies to attract investment, particularly foreign direct investment in projects developing alternative energy sources, including within regional integration unions (MERCOSUR, the Andean Community, the Pacific Alliance, CELAC, etc.); addressing natural and climatic challenges through the construction of energy storage facilities; increasing the role of national banks in addressing investment gaps in renewable energy projects; and enhancing international cooperation in developing renewable energy sources, both at regional and global levels.